African book market and its literary dynamics : the case of Cameroon - (:unkn) unknown (My University, 2013)
Since the eighties, international industrial firms enter North publishing houses' capital. This was the beginning of what is called book globalization. That process raises a standardization fear of published material; it also involves the emergence of thoughts and projects concerning bibliodiversity. In that context, African book's market has been structured in different kind of networks with the goal of sustaining its diffusion/distribution. On the end of the nineties, scholar researches increase their interest for African literature production's background. Behind each book, we find institutions, economies, authors' strategies, which are important to take in account. In this present work, we will consider the relations between African literary productions and Global book's market. Secondly, our work will focus on Cameroonian book's market as an editorial system, and will question its participation to the economy of literature at national, regional and international scales.
Keywords: African Research